PENGARUH KARAKTERISTIK INDIVIDU DAN MOTIVASI KERJA TERHADAP KINERJA DOSEN MELALUI KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL (Studi pada Dosen Universitas Sultan Fatah Demak) (Jurnal Mahasiswa Pasca Sarjana, 2013)
The purpose of this study is was to examine the effect of individual characteristic and work motivation to performance lecturer through job satisfaction and organisasional commitment. This research was conducted at Sultan Fatah Universty of Demak.Data on individual characteristic, work motivation, performance, job satisfaction and organisasional commitment is obstained through using a questionare to 110 respondent sample technique withdrawal with purposive from 135 population. Data were analyzed using analysis techniques with the help of Satistical Package for the Social Science (SPSS).The result showed Individual Characteristic and Work Motivation has a positive influence on job satisfaction. Individual Characteristic,Work Motivation, and Job Satisfaction has a positive influence on organisasional commitment. Individual Characteristic,Work Motivation, Job Satisfaction, organisasional commitment has a positive influence on performance.Based on the results of hyphotesis testing the problem of this study are Individual Characteristic has a not influence on lecturer performance in Sultan fatah University.  Keyword: Individual Characteristic, Work Motivation, Performance , Job Satisfaction Organisasional Commitment.